The Impact of Antipsychotic Treatment on Neurological Soft Signs in Patients with Predominantly Negative Symptoms of Schizophrenia - Cristian Petrescu; Ioana R. Papacocea; Crisanda Vilciu; Oana A. Mihalache; Diana M. Vlad; Gabriela Marian; Brindusa E. Focseneanu; Cristian T. Sima; Constantin A. Ciobanu; Sorin Riga; Adela M. Ciobanu (Biomedicines, 2022)
Schizophrenia is a complex and incompletely elucidated pathology that affects sensorimotor function and also produces numerous therapeutic challenges. The aims of this cross-sectional study were to identify the profile of neurological soft signs (NSS) in patients with predominantly negative symptoms of schizophrenia (PNS) compared with patients with schizophrenia who do not present a predominance of negative symptoms (NPNS) and also to objectify the impact of treatment on the neurological function of these patients. Ninety-nine (n = 99; 56 females and 43 males) patients diagnosed with schizophrenia according to DSM-V were included; these patients were undergoing antipsychotic (4 typical antipsychotics, 86 atypical antipsychotics, and 9 combinations of two atypical antipsychotics) or anticholinergic treatment (24 out of 99) at the time of evaluation, and the PANSS was used to identify the patients with predominantly negative symptoms (n = 39), the Neurological Evaluation Scale (NES) was used for the evaluation of neurological soft signs (NSS), and the SAS was used for the objectification of the extrapyramidal side effects induced by the neuroleptic treatment, which was converted to chlorpromazine equivalents (CPZE). The study’s main finding was that, although the daily dose of CPZE did not represent a statistically significant variable, in terms of neurological soft signs, patients with PNS had higher rates of NSS.